O17.2 Characterising clade-specific virus-host interactions in hiv infected clinically asymptomatic and aids presenting subjects. (13th September 2015) - Mathur, Abhilasha; Narang, Geetika; Sachdeva, Namrata; Kaur, Dashleen; Sachdeva, Neelam; Singh, Supriya
Abstract : Introduction: The utilised co-receptor is indicative of the clinical progression in HIV infected subjects. Differences in clades are known to impact the outcome of HIV infection. In this study, we investigated the utilised co-receptor and N-glycosylation sites in clinically asymptomatic and AIDS presenting subjects. Materials and methods: A total of 1, 538 nucleotide sequences encompassing the hyper-variable V3 loop of HIV-1, from clinically asymptomatic and AIDS presenting subjects were downloaded from the Los Alamaos Database, which belonged to clades A, B, C and D of HIV-1. Co-receptor prediction was performed using web-based tools PSSM and (ds) Kernel . Numbers of N-glycosylation sites were also calculated using the ' N-glycosite ' tool. Results: CCR5 was the utilised co-receptor in 97% (n = 200) of asymptomatic individuals of clade A and 96.5% (n = 199) of AIDS presenting subjects. In B-clade, 98.9% (n = 194) subjects in asymptomatic group were CCR5 utilising, and 83.5% of AIDS presenting subjects were CCR5 utilising (n = 163, CXCR4 were 22.3%, n = 47). In C-clade the CCR5 was utilised in 193 subjects (asymptomatic, n = 200), and 142 (AIDS presenting, n = 148) utilised both co-receptors (dual co-tropic), and in D clade the co-receptor utilised in 55% subjects was CCR5, n = 154 (CXCR4 in 45% subjects, n = 126), and 81% (n = 198) AIDS presenting subjects utilised CCR5, and 19% utilised CXCR4. Percentage of subjects exhibiting N-glycosylation sites also varied among clades with decrease in number of sites in some and increase in others, when compared between the two clinical categories. Conclusions: Co-receptor switching and addition of N-glycosylation sites does not seem to occur universally in all clades studied. The number of N-Glycosylation sites is also not increased from clinically asymptomatic to AIDS presenting subjects. In conclusion, co-receptor switching (from CCR5 to CXCR4) and increase in number of N-glycosylation sites, which are predictive of disease progression, does to occur in all clades universally, thus indicating clade specific responses.